2017
DOI: 10.1186/s12967-017-1176-x
|View full text |Cite
|
Sign up to set email alerts
|

Specific circulating microRNA signature of bicuspid aortic valve disease

Abstract: BackgroundWe aimed to determine the circulating miRNA expression profile associated with BAV and aortic dilation to provide diagnostic and prognostic biomarkers for BAV and/or aortic dilation.Methods and resultsWe applied a miRNome-wide microarray approach using plasma samples (n = 24) from healthy tricuspid aortic valve individuals, BAV patients and BAV patients with aortic dilation to compare and identify the specific miRNAs associated with BAV and aortic dilation. In a second stage, the expression patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 53 publications
4
69
0
Order By: Relevance
“…Furthermore, post-hoc subgroup comparisons revealed additional microRNA aberrations when comparing different valvulo-aortic phenotypes. These findings are similar to the previous studies which found differential expression patterns of microRNAs (i.e., miR-122, miR-130a, and miR-486) in specific valvulo-aortic phenotypes [27]. Consequently, our findings suggest that the correlation patterns between aortic diameters and circulating microRNAs may differ among the subgroups of underlying valvulo-aortic phenotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, post-hoc subgroup comparisons revealed additional microRNA aberrations when comparing different valvulo-aortic phenotypes. These findings are similar to the previous studies which found differential expression patterns of microRNAs (i.e., miR-122, miR-130a, and miR-486) in specific valvulo-aortic phenotypes [27]. Consequently, our findings suggest that the correlation patterns between aortic diameters and circulating microRNAs may differ among the subgroups of underlying valvulo-aortic phenotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the limited sample size and tentative approach, further investigations of larger multicenter cohorts are necessary to validate these promising findings. Recently, novel circulating miRNAs (miR-122, miR-130a, miR-486, and miR-718) were reported in association with BAV and aortopathy which were not included in our analysis [27]. Moreover, there is still no evidence that circulating miRNAs, which are associated with progressive aortopathy, arise specifically from the aortic tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The levels of miR-130a were up-regulated while levels of miR-122, 486 and miR718 were found to be down-regulated. This C-miR-NAs signature integrates these markers in the complex association of the bicuspid morphology of the aortic and the progressive dilation of the ascending aorta [131] and Refs in Table 1.…”
Section: Bicuspid Aortic Valve (Bav)mentioning
confidence: 96%
“…Recent studies revealed a significant association between downregulation of specific microRNAs and bicuspid aortopathy [17][18][19]. Martinez-Micaelo and coauthors applied a microarray approach to examining plasma microRNAs which could be specific for BAV and aortopathy [19].…”
Section: Circulating Micrornas and Bicuspid Aortopathymentioning
confidence: 99%
“…Recent studies revealed a significant association between downregulation of specific microRNAs and bicuspid aortopathy [17][18][19]. Martinez-Micaelo and coauthors applied a microarray approach to examining plasma microRNAs which could be specific for BAV and aortopathy [19]. They found that the expression levels of circulating miR-122, miR-130a, and miR-486 were significantly associated with aortic valve morphology (i.e., bicuspid vs. tricuspid), whereas the downregulation of circulating miR-718 strongly correlated with the proximal aortic diameter and ascending aortic dilation.…”
Section: Circulating Micrornas and Bicuspid Aortopathymentioning
confidence: 99%